EVALUATION OF ANALGESIC AND ANXIOLYTIC EFFECTS OF PEROVSKIA ABROTANOIDES IN SWISS ALBINO MICE - Marvi; kashif Iqbal; Arooj Mohsin Alvi; Maryum Mumshad Raja; Hassan Irfan; Ayesha Sana; Ayaz Ali Khan; Amanullah Sial (International Journal of Pharmacy & Integrated Health Sciences, 2025)
Background: Perovskia abrotanoides is a shrubby plant from a lesser-known genus within the Lamiaceae family, reputed for its notable medicinal qualities. It has been traditionally used for the treatment of liver problems, respiratory disorders, and several other illnesses. However, its analgesic and anxiolytic effects still need further exploration. Objectives: This research provides a thorough investigation into the analgesic and anxiolytic potential of Perovskia abrotanoides, commonly used due to its medicinal benefits. Methodology: Perovskia abrotanoides methanolic extract was subjected to an acute toxicity test to analyze the safety of Perovskia abrotanoides methanolic extract. Acute toxicity of the methanolic extract was evaluated in 25 male Swiss albino mice at dosages ranging from 250 to 2000 mg/kg. The analgesic efficacy of Perovskia abrotanoides methanolic extract was assessed through the acetic acid-induced writhing and formalin tests. The anxiolytic effect of Perovskia abrotanoides methanolic extract was evaluated through behavioural assessments, including the open field test, cage crossing test, rearing test, traction test, and forced swim test. Results: Acute toxicity studies indicated safe administration of Perovskia abrotanoides methanolic extract at 250-2000 mg/kg dose. Moreover, it exhibited a substantial analgesic effect, as evaluated through pain relief, comparable to that of aspirin. Additionally, mice administered Perovskia abrotanoides methanolic extract exhibited enhanced exploratory behavior and reduced immobility time, suggesting potential antidepressant-like properties. Conclusion: This research highlights the safety and therapeutic potential of Perovskia abrotanoides as a natural remedy for anxiety, depression, and pain, underscoring that its methanolic extract possesses significant analgesic and anxiolytic properties attributed to its bioactive components, which modulate inflammatory pathways and alleviate oxidative stress